Pay inequalities regarding nationality and gender using the example of social work and related professions - Mazari, Simone (Momentum Quarterly, 2024)
The article deals with wage inequality in the so-called care economy in Germany. This includes, among others, the fields of (dental) doctors, social workers and educators as part of the helping professions. The occupational designations are based on the designations from the quantitative material. These traditionally consist of a high proportion of women. Men and non-Germans are underrepresented. The focus is on social work, the other professions are chosen from a contrasting and complementary perspective and are within the spectrum of helping professions as (non-)academic professions. The central research question is the extent to which gender-specific pay inequality is evident here and how this is related to nationality. The data comes from a mix of methods. Categories of social stratification such as gender, class and ethnicity are not used singularly or additively, but are analyzed in their interconnectedness. To this end, the material is supplemented qualitatively, as the quantitative material unfortunately does not allow differentiation according to ethnicity or class. It can be stated that intersectionality is discussed here as a connection between gender and nationality on the basis of the available material.
Keywords: Pay Inequality; Intersectionality; Care Economy; Social Work; Helping Professions